2022
DOI: 10.2106/jbjs.21.01407
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Adhesive Capsulitis Suggests Significant Genetic Risk Factors

Abstract: Background: Adhesive capsulitis of the shoulder involves loss of passive range of motion with associated pain and can develop spontaneously, with no obvious injury or inciting event. The pathomechanism of this disorder remains to be elucidated, but known risk factors for adhesive capsulitis include diabetes, female sex, and thyroid dysfunction. Additionally, transcriptional profiling and pedigree analyses have suggested a role for genetics. Identification of elements of genetic risk for adhesive capsulitis usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
1
4
0
2
Order By: Relevance
“…The current paper by Bovonratwet et al at the Hospital for Special Surgery in New York provides the latest installment in a growing set of orthopaedic studies in this journal that investigate the relationship between genetic variations and the risk of surgery for spinal conditions. Similar to prior published efforts by Yanik et al 2 , Brüggemann et al 3 , and Kulm et al 4,5 , the study by Bovonratwet et al leverages the power of the UK Biobank, which has genetic data for about 400,000 patients, of whom a total of about 20,000 (∼5%) had 1 of 4 spinal conditions (i.e., lumbar spondylolisthesis, spinal stenosis, degenerative disc disease, and pseudarthrosis after spinal fusion). Results from this large data set (“training population”) were then tested using the FinnGen database (“test population”) for validation.…”
Section: Commentarysupporting
confidence: 82%
See 1 more Smart Citation
“…The current paper by Bovonratwet et al at the Hospital for Special Surgery in New York provides the latest installment in a growing set of orthopaedic studies in this journal that investigate the relationship between genetic variations and the risk of surgery for spinal conditions. Similar to prior published efforts by Yanik et al 2 , Brüggemann et al 3 , and Kulm et al 4,5 , the study by Bovonratwet et al leverages the power of the UK Biobank, which has genetic data for about 400,000 patients, of whom a total of about 20,000 (∼5%) had 1 of 4 spinal conditions (i.e., lumbar spondylolisthesis, spinal stenosis, degenerative disc disease, and pseudarthrosis after spinal fusion). Results from this large data set (“training population”) were then tested using the FinnGen database (“test population”) for validation.…”
Section: Commentarysupporting
confidence: 82%
“…Technological advances that allow cost-effective DNA sequencing have made it feasible to compare large patient populations matched on the basis of specific codes for medical conditions. Consequently, several studies have made impressive attempts at defining genetic variations linked to a range of surgically relevant musculoskeletal complications, including degenerative rotator cuff disease 2 , arthroplasty 3 , adhesive capsulitis of the shoulder 4 , and end-stage knee osteoarthritis 5 .…”
Section: Commentarymentioning
confidence: 99%
“…Angesichts der Pathophysiologie ist anzunehmen, dass genetische Polymorphismen in diesen Mechanismen die Entstehung der Erkrankung begünstigen. Hierbei wurden u. a. genetische Polymorphismen bei IL-6, MMP sowie TGF-β1 aber auch im wnt-Signalweg beschrieben, die sowohl bei der primären als auch bei der sekundären Schultersteife involviert zu sein scheinen [5,14,15]. Weiterhin wurde in einer Genomstudie eine van…”
Section: Genetische Faktorenunclassified
“…Die ethnische Herkunft hat einen Einfluss, außerdem besteht eine signifikant höhere Rate von HLA-B27-Positivität bei Patienten mit primärer Schultersteife. Die genauen molekulargenetischen Mechanismen oder Gen-Loci waren bisher nicht bekannt [7], inzwischen (nach Veröffentlichung der Leitlinie) wurden 3 Gen-Loci identifiziert, die in der Pathogenese der Frozen Shoulder eine Rolle spielen [8].…”
Section: Terminologie äTiologie Und Begleiterkrankungenunclassified
“…Ethnicity has an influence, and there is a significantly higher rate of HLA-B27 positivity in patients with primary shoulder stiffness. The exact molecular genetic mechanisms and gene loci were previously unknown [7], but in the meantime (after the publication of the guideline), three gene loci have been identified that play a role in the pathogenesis of frozen shoulder [8].…”
Section: Terminology Aetiology and Comorbiditiesmentioning
confidence: 99%